Sonidegib for the Treatment of Advanced Basal Cell Carcinoma - Brancaccio, Gabriella; Pea, Federico; Moscarella, Elvira; Argenziano, Giuseppe (Frontiers in Oncology, 2020)
Basal cell carcinoma (BCC) accounts for almost the 80% of skin cancers and its healthcare workload burden is substantial within dermatology departments. Although most BCCs are small, well-defined tumors amenable of surgery or conservative procedures, in a small proportion of patients BCCs can progress to an advanced stage including locally advanced BCC. The goal of the clinician in the treatment of BCC should be the right therapeutic approach at diagnosis, and different guidelines propose treatment strategies in order to prevent relapses or disease progression. In case of unresectable and untreatable BCC with radiotherapy, the first-choice medical therapy is HH pathway inhibitors. Sonidegib was approved by the FDA and EMA as a first-line treatment for adult patients with locally advanced BCC, becoming the second HH pathway inhibitor receiving approval after vismodegib. In this review, data on pharmacology, safety, tolerability and efficacy of sonidegib are summarized and compared to those vismodegib. Lastly, indications on the management of advanced basal cell carcinoma based on author’s clinical experience are provided.